Counselor training and attitudes toward pharmacotherapies for opioid use disorder. Issue 1 (2nd January 2016) - Aletraris, Lydia; Edmond, Mary Bond; Paino, Maria; Fields, Dail; Roman, Paul M.
ABSTRACT: Background : Methadone and buprenorphine have been demonstrated to be effective in the treatment of opioid use disorder (OUD), especially when combined with psychosocial treatment. Despite buprenorphine's association with fewer withdrawal symptoms and lessened risk of abuse, compared with methadone, its adoption remains limited. Given the vital role that counselors may play in its successful implementation, their knowledge and perceptions of opioid agonist therapy may be facilitators or barriers to its acceptance. Methods : Informed by diffusion theory, the current study examined perceptions of buprenorphine's and methadone's acceptability among 725 counselors employed in a nationally representative sample of substance use disorder treatment centers. First, we provided descriptive statistics about medication diffusion, extent of training received about the medications, and perceptions of acceptability of each medication. Then, we compared acceptability of opioid agonists with other treatment approaches for OUD. Finally, we conducted 2 ordinary least squares regressions to examine counselor acceptability of buprenorphine and of methadone. Results : Descriptive statistics suggested that diffusion of information about buprenorphine and methadone was not complete, and training was not extensive for either medication. Counselors reported greater acceptability and training of buprenorphine compared with methadone. Methadone was rated as the least acceptable among all other treatment approaches. Multivariate analyses indicated regional differences, and that medication-specific training, adaptability, and educational attainment were positively related with perceptions of acceptability of either medication, even after controlling for organizational characteristics. Adherence to a 12-step orientation was negatively associated with acceptability. Conclusions : Dissemination of information about opioid agonist therapy is occurring. Nevertheless, the fact that 20% of counselors admitted not knowing enough about either buprenorphine's or methadone's effectiveness is surprising in light of the extensive literature documenting their effectiveness. Future research should focus upon different types of training that can inform physicians, counselors, and patients about the use of opioid agonist therapy.